Hybrid protocol for wireless EH network over weibull fading channel: performance analysis - Phu Tran Tin; Tan N. Nguyen; Tran Thanh Trang (Institute of Advanced Engineering and Science, 2020)
In this paper, the hybrid TSR-PSR protocol for wireless energy harvesting (EH) relaying network over the Weibull fading channel is investigated. The system network is working in half-duplex (HD) mode. For evaluating the system performance, the closed-form and integral-form expressions of the outage probability (OP) are investigated and derived. After that, numerical results convinced that our derived analytical results are the same with the simulation results by using Monte Carlo simulation. This paper provides a novel recommendation for the wireless EH relaying network.